Impact of physical match performance on youth futsal talent program selection: a detailed analysis by team rank in Portugal - Ribeiro, J. N.; Yousefian, F.; Arede, J.; Sarmento, H.; Leite, N.; Travassos, B. (Research Quarterly for Exercise and Sport, 2025)
This study examined the physical match performance of male youth futsal players in Portugal, focusing on their team ranks and participation in the National Team Development Program (NTDP) selection. Data on locomotor activity was gathered using local positioning system devices during a four-day under-15 regional inter-association competition involving 202 players from 22 teams categorized into three national ranks: R1 (top), R2 (middle), and R3 (bottom). The physical performance metrics were collected: total distance covered (TD; in meters), low-intensity running (LIR, 0-12 km/h), medium-intensity running (MIR, 12.1-18 km/h), and high-intensity running (HIR, 18.1-30 km/h). Linear mixed model analyses revealed that players in R1 and R2 exhibited significantly greater relative intensities (meters per minute) and higher percentages of MIR and HIR compared to those in R3 (p = .001; ES: 0.4-1.1). In terms of selection status, players selected for the NTDP demonstrated superior absolute total distance (TD) and relative intensities across various running categories (LIR, MIR, and HIR) compared to non-selected players (p = .01; ES: 0.7-1.7). These findings underscore the correlation between higher performance metrics and team rankings, emphasizing the need for targeted training to enhance HIR performance, ultimately aiding in the development of youth futsal players and informing elite coaches` selection processes for the NTDP.